Effects of fenton system on recycled unbleached pulp in absence and presence of p-Hydroxybenzoic acid - Mocchiutti, Paulina (2010)
The effects of the Fenton reagent on recycled unbleached pulp in the absence and presence of a model chemical contaminant, the p-hydroxybenzoic acid (HBA), were studied. In the absence of HBA, the Fenton system clearly modified the chemical and papermaking properties of the pulp. The kappa number was reduced and the specific light absorption coefficient was increased, indicating lignin modification. The amount of total acid groups increased, suggesting lignin or carbohydrate oxidation. Pulp freeness and wet tensile strength were significantly improved, while short compressive strength was slightly increased. Nevertheless, dry tensile strength decreased. In the presence of HBA, the chemical and papermaking properties of the pulp were less modified. When a higher ferrous ion charge was applied, half of the HBA present in pulp was eliminated while, at a lower ferrous ion charge, a lower reduction in HBA was produced, pulp strength being nevertheless preserved.